Long noncoding RNA UCA1 from hypoxia-conditioned hMSC-derived exosomes: a novel molecular target for cardioprotection through miR-873-5p/XIAP axis - Sun, Ling; Zhu, Wenwu; Zhao, Pengcheng; Wang, Qingjie; Fan, Baohan; Zhu, Yeqian; Lu, Yao; Chen, Qiushi; Zhang, Jian; Zhang, Fengxiang (Cell death & disease, 2020)
Exosomes (Exo) secreted from mesenchymal stem cells (hMSCs) are protective against myocardial injury. The purpose of the study was to investigate the role and mechanisms by which exosomes promote cardiomyocyte survival and function following myocardial infarction (MI). hMSCs were cultured under hypoxic and normoxic conditions. Hypoxia-conditioned hMSC-derived exosomes (Hypo-Exo) and normoxic-conditioned hMSC-derived exosomes (Nor-Exo) were collected and intramyocardially injected into rats with MI. The therapeutic effects of Hypo-Exo and Nor-Exo were evaluated after 4 weeks. Quantitative real-time PCR (qRT-PCR) was used to detect the expression of candidate long noncoding RNA urothelial carcinoma associated 1 (lncRNA-UCA1) in Nor-Exo and Hypo-Exo. Intramyocardial injection of lncRNA-UCA1-knockdown-Hypo-Exo in a rat model of MI was then performed and the cardiac function was characterized. The target and downstream of the molecular mechanism lncRNA-UCA1 was disclosed by luciferase reporter assays and western blot. Circulating exosomal lncRNA-UCA1 level in AMI patients and healthy volunteers was assessed. We found that (1) hMSC exosomal (from hypoxic and normoxic conditions) cardioprotection in vitro and in vivo correlated with the presence of encapsulated lncRNA-UCA1 in exosomes; (2) lncRNA-UCA1 targeted miR-873 via sponging, reducing the latter’s suppressive effects on its target XIAP, and this translated into AMPK phosphorylation and increased level of the antiapoptotic protein BCL2; and (3) plasma derived from patients with AMI contained exosomes enriched with the lncRNA-UCA1, unlike that from normal subjects. This study demonstrates that Hypo-Exo lncRNA-UCA1 plays a cardioprotective role via the miR-873-5p/XIAP axis and circulating exosomal lncRNA-UCA1 may be a promising novel biomarker for the diagnosis of AMI.